The Effect of Nutrition Educational Programs on the Composition of Home Prepared Children’s Breakfasts - Ayala Raviv; Ester Aflalo (Athens Journal of Education, 2022)
The study aimed to examine the effectiveness of two intervention programs in improving dietary habits in two groups of preschool and fifth-grade students. The programs were tailored to the target age group. The composition of each of the children’s breakfasts that were brought from home was recorded both before and after the intervention program. Every food item received a score according to its nutritional quality, and each meal was summed accordingly. T-tests were performed in order to determine the significance of differences between the nutritional quality of the children’s breakfast items before and after the intervention. It was found that the nutritional quality of all breakfast components and its overall health quality improved significantly in both age groups. The study’s results indicate that the intervention program is effective for a range of young ages. It is recommended to conduct such programs starting in preschools, and subsequently in schools.